ENHANCED A CHARACTER EDUCATION SINGLE-PARENT FAMILIES - Utami, Rahayu Dwi; Nofianti, Rita; Febriana, Dora (Proceeding International Conference of Science Technology and Social Humanities; Vol 1 (2022): International Conference of Science Technology and Social Humanities, 2023)
Enhancing character education within single-parent families is of utmost importance. Introducing and cultivating character education in young children should be prioritized from an early age. The early stages of infancy offer optimal opportunities for providing meaningful emotional stimulation. Exploring the parenting techniques within single-parent households can contribute to character education for children. This research utilizes a qualitative approach with a focus on phenomenology. Primary and secondary data sources, including observations, interviews, and documents, were employed to gather relevant information on this research topic. The interactive analytical model developed by Miles and Huberman was utilized to analyze the data, employing techniques such as data reduction, data visualization, and data verification to draw conclusions. The primary finding of this study reveals that despite their limitations in terms of knowledge and experience, single-parent households place significant emphasis on character education during early childhood. Religious teachings and imparting the importance of discipline are integral aspects of character education. However, economic and sociocultural barriers hinder single-parent households from dedicating sufficient quality time to their children's meaningful character development.